Pulse processing affects gas production by gut bacteria during in vitro fecal fermentation. (September 2021) - Rose, Devin J.; Poudel, Rachana; Van Haute, Mallory J.; Yang, Qinnan; Wang, Lei; Singh, Mukti; Liu, Sean
Graphical abstract: Highlights: Processing could be a way to reduce gas production by the microbiome. Germination reduced gas production the most among six processing methods. Germination also reduced abundance of Bacteroides and Lachnospiraceae. Germination also reduced production of beneficial microbial metabolites. Abstract: Flatulence is one barrier to pulse consumption for many people. Therefore, we examined how processing affects gas production by the microbiome in three classes of pulses. Processing did not affect gas production from Navy beans. However, in Pardina lentils and green peas, (−1.9 ± 0.3 mL/24 h, p < 0.001; −2.3 ± 0.3 mL/24 h, p < 0.001, respectively). In Pardina lentils and green peas, germination diminished carbohydrate utilization by the microbiome compared with unprocessed samples. In Pardina lentils germination reduced abundance germination resulted in the greatest reduction in gas production among six processing methods of amplicon sequence variants (ASVs) from Bacteroides and Lachnospiraceae and reduced propionate production compared with unprocessed samples. In green peas, germination reduced ASVs from Lachnospiraceae, including one from Roseburia, and reduced proportion of butyrate production during fermentation. Three ASVs from Clostridium sensu stricto (cluster 1), Megasphaera elsdenii, and unclassified Veillonellaceae, were strongly associated with increased gas production across all samples (ρ = 0.67–0.69, p < 0.001). This study showed that processing can reduce gas production by the microbiome in some pulses, but also reduces saccharolytic fermentation and production of beneficial microbial metabolites.